The Impact of Functional Overreaching on Post-exercise Parasympathetic Reactivation in Runners - Bellenger, Clint R.; Thomson, Rebecca L.; Davison, Kade; Robertson, Eileen Y.; Buckley, Jonathan D. (Frontiers in Physiology, 2021)
While post-exercise heart rate (HR) variability (HRV) has been shown to increase in response to training leading to improvements in performance, the effect of training leading to decrements in performance (i.e., overreaching) on this parameter has been largely ignored. This study evaluated the effect of heavy training leading to performance decrements on sub-maximal post-exercise HRV. Running performance [5 km treadmill time-trial (5TTT)], post-exercise HRV [root-mean-square difference of successive normal R-R intervals (RMSSD)] and measures of subjective training tolerance (Daily Analysis of Life Demands for Athletes “worse than normal” scores) were assessed in 11 male runners following 1 week of light training (LT), 2 weeks of heavy training (HT) and a 10 day taper (T). Post-exercise RMSSD was assessed following 5 min of running exercise at an individualised speed eliciting 85% of peak HR. Time to complete 5TTT likely increased following HT (ES = 0.14 ± 0.03; p < 0.001), and then almost certainly decreased following T (ES = −0.30 ± 0.07; p < 0.001). Subjective training tolerance worsened after HT (ES = −2.54 ± 0.62; p = 0.001) and improved after T (ES = 2.16 ± 0.64; p = 0.004). In comparison to LT, post-exercise RMSSD likely increased at HT (ES = 0.65 ± 0.55; p = 0.06), and likely decreased at T (ES = −0.69 ± 0.45; p = 0.02). A moderate within-subject correlation was found between 5TTT and post-exercise RMSSD (r = 0.47 ± 0.36; p = 0.03). Increased post-exercise RMSSD following HT demonstrated heightened post-exercise parasympathetic modulation in functionally overreached athletes. Heightened post-exercise RMSSD in this context appears paradoxical given this parameter also increases in response to improvements in performance. Thus, additional measures such as subjective training tolerance are required to interpret changes in post-exercise RMSSD.